Analysis of the integrin β3 receptor for pathogenic orthohantaviruses in rodent host species - Müller, Alexander; Baumann, Alexandra; Essbauer, Sandra; Radosa, Lukáš; Krüger, Detlev H.; Witkowski, Peter T.; Zeier, Martin; Krautkrämer, Ellen (Virus research, 2019)
Host reservoir specificity of pathogens is complex and may depend on receptor variability. For pathogenic orthohantaviruses, integrin β3 had been previously identified as entry receptor and the presence of aspartic acid residue at position 39 (D39) in human integrin β3 was described to be a prerequisite for infection of primate cells with Hantaan virus (HTNV). However, the role of integrin β3 in orthohantavirus infection of host animals is not completely understood. Therefore, we analyzed the nucleotide sequence of the integrin β3 gene of Myodes glareolus and Apodemus agrarius, the hosts of Puumala virus (PUUV) and HTNV, respectively. Sequence analysis in tissue samples demonstrated that the amino acid residue D39 is not present in integrin β3 of these natural orthohantavirus hosts. Furthermore, we analyzed the transcription and protein expression levels of integrin β3 in the renal cell line BVK168 generated from the PUUV host, bank vole. Transcription level of integrin β3 was 100-fold lower in BVK168 cells than in Vero E6 cells and integrin β3 expression was not detectable in BVK168 cells. However, despite the absence of amino acid residue D39 and no detectable integrin β3 expression, BVK168 cells are susceptible to infection with both PUUV and HTNV. These results indicate that the mechanism of orthohantaviral entry in rodent species does not correspond to the requirements that were described for the entry in primate cells in vitro.
Gesehen am 27.11.2019